Pulmonary veins isolation with non-irrigated ablation catheters - Doronin, A.; Suslina, Y.; Riznyk, A.; Khanenova, V.; Marushko, Y.; Meshkova, M. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The article analyzes our own experience of the pulmonary veins isolation during radiofrequency catheter ablation of atrial fibrillation (AF) with 4 mm tip non-irrigated catheters. The results of 145 primary AF catheter ablations in consecutive patients with paroxysmal AF have been analyzed. During the procedure after each 15–20 applications the ablation catheter was removed and wiped with a damp cloth. The average time of X-ray exposure was 25.2±6.3 min. The recurrence of AF in 1 year after ablation occurred in 43 (29.7%) patients, another 1 (0.7%) had a typical atrial flutter, 1 – atrial tachycardia, 1 – left atrial flutter. Sinus rhythm has been preserved without the use of antiarrhythmic drugs during the 1 year after procedure in 99 (68.3%) patients. There were 4 (2.8%) complications: 2 (1.4%) cases of pericardial tamponade treated with pericardiocentesis and 2 (1.4%) cases of pericardial effusion, which were treated conservatively. Thus, this technique is quite effective and safe.